Design and fabrication of a novel spinning fluidised bed - Taib, Mohamad Rozainee (Universiti Teknologi Malaysia, 2002)
Existing vertical spinning fluidised bed (SFB) have several drawbacks, such as non-uniform radial and axial bed fluidisation, feeding and ash accumulation problems. The purpose of this research, therefore is to develop a prototype of the horizontal SFB combustor capable of overcoming these drawbacks. The scopes of the research include engineering design of the prototype, computational fluid dynamics (CFD) modelling and set-up/commissioning of the developed prototype. Under this research, a prototype of the horizontal SFB has been successfully developed and is able to overcome the inherent weakness in vertical SFB. The innovative secondary chamber provides more freeboard for more complete combustion and acts as particulate control device. The prototype is suitable for burning low-density materials (rice husk, fibrous materials), which are difficult to be burnt in conventional fluidised bed by imparting a higher centrifugal force. There is also no limit to the amount of air throughput and combustion is only limited by the kinetics in which each different type of waste burns. Results from the CFD modelling narrowed down the parameters to be tested on the SFB in future experimental works, as well as providing design improvements on the current SFB design. Due to its compactness and versatility in burning a wide range of waste, the SFB prototype has the potential to be utilised as small-scale on-site waste incineration facility and high-efficiency gas burner for high-loading waste gas streams in chemical plants or refineries. The whole system is mountable to a truck and can be transported to waste sources such as rice mills, sawmills, wastewater treatment plants to incinerate waste. The full performance on the developed SFB during combustion of various types of wastes is outside the scope of the current research and therefore, is subjected to future experimental works.